Extreme Weather and Poverty Risk : Evidence from Multiple Shocks in Mozambique - Baez, Javier E. (World Bank, Washington, DC, 2019)
Thanks to strong economic growth over the last two decades, poverty in Mozambique has decreased and the average household is now more likely to access basic education, health, and housing. Yet, the country is still ravaged by intense and frequent weather disasters. To determine the scale and nature of the impacts of these shocks, this paper analyzes the vulnerability of rural livelihoods across three different extreme weather events: droughts, floods and cyclones. The study finds that per capita food and non-food consumption and asset ownership are reduced among households affected by any of the three weather shocks. Their children are less likely to attend school, have a higher probability of falling sick and show higher engagement in paid and unpaid work. What’s more, staple food prices are disrupted and remain affected nearly a year after the disaster. Helping households confront these events requires comprehensive risk management policies, including making agriculture more resilient to weather, improving the functioning of credit and insurance markets, facilitating economic diversification and market access, and increasing the availability of flexible safety nets – all before the shocks occur.